2016
DOI: 10.1186/s12957-016-1033-z
|View full text |Cite
|
Sign up to set email alerts
|

The expression of metastasis-associated in colon cancer-1 and KAI1 in gastric adenocarcinoma and their clinical significance

Abstract: BackgroundThe most common reason for malignant tumor treatment failure is recurrence and metastasis. Metastasis-associated in colon cancer-1 (MACC1) was originally identified as a metastatic and prognostic biomarker for colon cancer and later other solid tumors. Kangai 1 (KAI1), a marker of suppressor of metastasis, is also associated with metastasis and poor prognosis in many tumors. However, the prognostic value of either MACC1 or KAI1 in gastric adenocarcinoma (GAC) is unclear. In this study, we explored th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…CD44 overexpression is beneficial to CAC progression and metastasis. During cancer progression, MACC1 overexpression should inhibit cancer cell apoptosis and promote cancer cell EMT via HGF/MET pathways [ 32 , 33 ]. Twist1 overexpression could further promote the cancer cell EMT process through regulating E-cadherin, N-cadherin, and MMP expression [ 21 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…CD44 overexpression is beneficial to CAC progression and metastasis. During cancer progression, MACC1 overexpression should inhibit cancer cell apoptosis and promote cancer cell EMT via HGF/MET pathways [ 32 , 33 ]. Twist1 overexpression could further promote the cancer cell EMT process through regulating E-cadherin, N-cadherin, and MMP expression [ 21 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showing the elevated expression of claudin-1, −3 and −4, EpCAM, E-cadherin in colon cancer were consistent with earlier studies [11,22,23] . Previously it was shown that decreased expressions of CD9 [24] and CD82 were vital for colon cancer metastasis, and particularly reduced expression of CD82 was related with metastatic colon [25] and gastric cancer [26]. Here, we have also identified expression changes in seven PKC isoforms in both normal colon cells and colon cancer cells.…”
Section: Discussionmentioning
confidence: 55%
“…After screening the titles and abstracts, nine eligible studies were included in the meta-analysis. 9,10,14,[16][17][18][19][20][21] The characteristics of selected studies are summarized in Table 1. All the included studies were performed retrospectively and published between 2011 and 2018.…”
Section: Literature Retrieval and Analysismentioning
confidence: 99%